Assessing Local Hijrah Movement’s Persistance: Rabbani Generation Community in Langsa, Aceh, Indonesia - Darwin, Rizkika Lhena; Melly Masni (Vox Populi, 2024)
This paper attempts to assess the persistence of a Hijrah movement, the Rabbani Movement Community (KGR, ‘Komunitas Gerakan Hijrah’) in Langsa, Aceh, using social movement theory. In the midst of the growing trend of the Hijrah movement at the national level, it is intriguing to comprehend the existence of local Hijrah movements, particularly those with movement bases in areas where Islamic sharia is applied, such as Aceh. This region is believed to have a political opportunity structure that optimally supports the continuation of movements whose central tenets are Islamic values. However, KGR shows the opposite fact. Using a qualitative approach consisting of in-depth interviews and documentation, the research reveals that although the existence of KGR is strongly supported by a conducive political opportunity structure in Aceh and the framing of Islamic values that encourage widespread social acceptance of the Acehnese people, its consistency in terms of resource mobilization is weak, making it difficult for this movement to maintain its existence. This is due to the KGR's excessive dependence on its founder, which makes the movement vulnerable without the drive of its most influential figure.